Personality Development from Age 12 to 25 and its Links with Life Transitions. Issue 3 (May 2020) - Van Dijk, Marloes P.A.; Hale, William W.; Hawk, Skyler T.; Meeus, Wim; Branje, Susan
During adolescence and young adulthood, individuals show personality changes and experience various life transitions. Whereas personality might affect the timing of life transitions, life transitions might also induce personality maturation. We examined Big Five personality maturation from age 12 to 25 using a 9–year longitudinal study of Dutch youths from two cohorts ( n 1 = 683, M ageT1 = 12.70; n 2 = 268, M age T1 = 16.87). We linked personality maturation to the incidence and timing of four transitions: first romantic relationship, leaving the parental home, first job, and first cohabitation or marriage. Results indicated increases in mean levels, rank–order stabilities and profile stability of personality between age 12 and 25, which were largely replicated across the cohorts. Very few associations between personality and life transitions existed. However, higher mean–level Extraversion predicted leaving the parental home and starting the first romantic relationship, an earlier age when starting the first job, and an earlier average timing of transitions. Regarding social investment effects, we only found that those who never experienced a romantic relationship at age 25 decreased, while those who did increased in profile stability over time. These results suggest that personality consistently matures during adolescence and young adulthood and that higher Extraversion predict greater readiness for new steps towards adulthood.